Comparison of the Chondrogenic Differentiation Potential of Equine Synovial Membrane-Derived and Bone Marrow-Derived Mesenchymal Stem Cells - Gale, Alexis L.; Linardi, Renata L.; McClung, George; Mammone, Renata M.; Ortved, Kyla F. (Frontiers in Veterinary Science, 2019)
Focal cartilage injury occurs commonly and often precipitates OA. Mesenchymal stem cells (MSCs) may be useful for repairing cartilage lesions, thereby preventing joint degeneration. Although MSCs isolated from bone marrow have been shown to have chondrogenic potential, synovial membrane-derived MSCs (SM-MSCs) may have superior chondrogenic abilities due to a common progenitor cell between synovium and cartilage. The objective of this study was to directly compare the immunophenotype, proliferative capabilities, and chondrogenic potential of equine SM-MSCs and bone marrow-derived MSCs (BM-MSCs). In order to do this, MSCs were isolated from synovial membrane and bone marrow collected from 6 adult horses. Flow cytometric analysis was used to assess cell surface marker expression including CD29, CD44, CD90, CD105, CD45, CD-79α, MHCI and MHCII. Proliferation rates and doubling time were quantified in P1 and P2 cells. Trilineage differentiation assays were performed. MSC pellets were cultured in chondrogenic induction media for 28 days. Pellets were stained with toluidine blue to assess proteoglycan deposition. Expression of the chondrogenic-related genes ACAN, COL2b and SOX9 was quantified using qRT-PCR. The immunophenotypes of BM-MSCs and SM-MSCs were similar with both cell types being positive for expression of stem cell markers (CD29, CD44, CD90, CD105, and MHCI) and negative for exclusion markers (CD45 and CD79α). Although SM-MSCs did not express the exclusion marker, MHCII, expression of MHCII was moderate in BM-MSCs. Overall, chondrogenic differentiation was not significantly between the cell types with histologic parameters, proteoglycan content and gene expression being similar. BM-MSCs showed enhanced osteogenic differentiation compared to SM-MSCs. Synovial membrane is a feasible source of MSCs in the horse, however, superior chondrogenesis in vitro should not be expected under currently described culture conditions.